FUSI CITRA DENGAN TRANSFORMASI WAVELET - Fitria, Ressy
Image fusion is a technique to combine images to acquired a new single image with a better quality information. There are studies that have been done in this field, such as spatial and visual enhancement satellite image. Various techniques were used. One of these techniques is the wavelet transform. In this research, the wavelet transform was applied to detect the pressence of cloud and to accomplish the image fusion. The goal of image fusion in this research is to refill cloud pixels in Landsat 8 image with those from a cloud free image. The other approaches was also applied in cloud detection. Comparing these techniques, the wavelet approach performs better than other. In the term of image fusion, the 1st level decomposition give better result than the 2nd level decomposition.